Design and Performance Test of Horizontal Type Ginger Chopper Machine - Agus Sutejo; Abdul Khair (abe.fp.unila.ac.id, 2022)
Ginger is a horticultural plant that can be used as a spice or medicine. Slicing is the process of reducing the size by using a knife to get the length of the pieces that are smaller and thinner in a transverse, oblique or parallel direction to the material to be cut. The traditional slicing process is still relatively time consuming so it is not practical and cannot meet the needs. This study aims to design and performance test slicing machine type horizontal for red ginger and elephant ginger. The design is carried out on the hopper component and slicing system. The slicing performance test was carried out at rotational speeds of 46.67 rpm, 56 rpm and 65.33 rpm using 2 and 4 slicing blades with three replications. The results of the design show that the hopper using a clamping system can accommodate 13 kg of ginger. The testing results of the slicing system got the largest machine performance efficiency of 87.4% at rotational speed of 56 rpm with 2 blades with a slicing of 262 kg/hour. This slicing is very large compared to traditional slicing (3 kg/hour) and greater than previous studies with a slicing machine that uses a pressing mechanism (128 kg/hour).